Evaluating the Relative Efficiency of Bank Branches by Using the COOPER-Framework - Cvetkoska, Violeta (My University, 2015)
The aim of the paper is to evaluate the relative efficiency of the branches of Komercijalna Banka AD Skopje in the period between 2009 and 2011 by using the COOPER-framework. In the conducted research the six phases of the framework are being followed. In the first phase (Concepts and objectives) information regarding the profile of the bank branches is gained, and the aims of the empirical study are defined, as well as the aim of using the non-parametric approach DEA. In the second phase (On Structuring data) the inputs and outputs are chosen, and the database is prepared. In the third phase (Operational models) the DEA model is specified, while in the fourth phase (Performance comparison model) the returns to scale and orientation of the model are specified. Since the number of bank branches is small, in regards to the chosen inputs and outputs, it is decided that the DEA technique Window Analysis be used for its growth. Additionally, it is in the fourth phase that the model is solved by using the software tool EMS. In the fifth phase (Evaluation) the obtained results are presented to the bank, and it is concluded that they reflect the real situation. In the last phase (Results and deployment) it is suggested in the bank to use the developed model continuously in order to improve the efficiency of the branches that are identified as relatively inefficient.
Keywords: efficiency, bank branches, COOPER-framework, DEA